Dynamic responses of space solar arrays considering joint clearance and structural flexibility. (June 2016) - Li, Yuanyuan; Wang, Zilu; Wang, Cong; Huang, Wenhu
This article numerically investigates the effects of revolute joint clearance and structural flexibility on the overall dynamic characteristics of a deployable solar array system. Considering torque spring, close cable loop configuration, and lock mechanism, a typical mechanism composed of a main body with a yoke and two panels is used as a demonstration case to study the effects of clearance and flexibility on the dynamic response of the deployable solar array system in the deployment and lock process. The normal contact force model and tangential friction model in clearance joint are established using Lankarani Nikravesh model and modified Coulomb friction model, respectively. The numerical simulation results reveal that the coupling of clearance and flexibility makes different effects on the dynamic characteristics of the deployable space solar arrays for different operation stages. Besides, the clearance and flexibility of a mechanical system play crucial roles in predicting accurately the dynamic response of the system, which is the foundation of mechanism design, precision analysis, and control system design.